2004
DOI: 10.1002/hup.583
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of the platelet 5‐HT2A receptor function by long‐term imipramine treatment in endogenous depression

Abstract: The results showed a decrease in a platelet functional response mediated by 5-HT2A receptors following effective imipramine treatment, suggesting that desensitization or down-regulation of the 5-HT2A receptor function could be linked to the therapeutic effect of some antidepressants. The data also support the use of platelet aggregometry as a surrogate measurement of antidepressant action, particularly in intra-subject designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…+++p < 0.001 in comparison with the cinanserin group. ###p < 0.001 and #p < 0.05 in comparison with the ARS group inhibition as well as enhancement of BDNF levels could induce antidepressant-and anxiolytic-like responses (Dos Santos et al 2016a;Gomez-Gil et al 2004). Moreover, the obtained results revealed that there was an interaction between the harmaline and 5-HT2 receptor on the modulation of depression-and anxiety-like behaviors in the ARS mice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…+++p < 0.001 in comparison with the cinanserin group. ###p < 0.001 and #p < 0.05 in comparison with the ARS group inhibition as well as enhancement of BDNF levels could induce antidepressant-and anxiolytic-like responses (Dos Santos et al 2016a;Gomez-Gil et al 2004). Moreover, the obtained results revealed that there was an interaction between the harmaline and 5-HT2 receptor on the modulation of depression-and anxiety-like behaviors in the ARS mice.…”
Section: Discussionmentioning
confidence: 77%
“…Since anxiety is a symptom commonly observed in depressed patients after the acute application of SSRIs, the beneficial effects of 5-HT2 receptor antagonists on the antidepressant response could involve anxiolytic behaviors (Dekeyne et al 2008). Researches revealed that the desensitization or downregulation of 5-HT2 receptors could be related to the therapeutic properties of some antidepressants (Gomez-Gil et al 2004). Imaging studies supported this hypothesis because the downregulation of the 5-HT2 receptor was identified in the brain of depressed patients in response to SSRI treatment (Meyer et al 2001).…”
Section: Discussionmentioning
confidence: 96%
“…In considering changes at the 5HT2A receptor as a potential mechanism of action: cortical 5HT2A receptor expression is increased in postmortem samples of patients with depression who display suicidality (Mendelson, 2000; Pandey et al, 2002; Shelton et al, 2009); depressed patients with elevated pessimism display increased PFC 5HT2A receptor binding compared to control participants (Bhagwagar et al, 2006; Meyer, 2012; Meyer et al, 2003); and sustained treatment with various anti-depressants (e.g. selective serotonin reuptake inhibitors, tricyclic anti-depressants) have been associated with a reduction of 5HT2A receptor density (Gomez-Gil et al, 2004; Yamauchi et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Using drugs with significant antagonistic properties toward the 5-HT 2A receptor (mianserin and mirtazapine), in addition to selective serotonin reuptake inhibitor (SSRI)s enhanced therapeutic responses in patients with major depression. 22,23) In an animal study, a reduction in the number of 5-HT 2A receptors caused by the administration of an antisense oligonucleotide decreased the duration of immobility in the forced swim test in mice.…”
Section: Discussionmentioning
confidence: 99%